Attitudes, perceptions, and experiences of Western Australians towards vaccine safety surveillance systems following COVID-19 vaccines: A qualitative descriptive study - Denis Liu Shiu Cheong; Jayden Tran; Wyitt Chong; Scott May; Samantha J. Carlson; Sandra M. Salter; Katie Attwell (Elsevier, 2024)
Objective: Concerns regarding adverse events following immunisation (AEFI) are a barrier to vaccine uptake. Health professionals use vaccine safety surveillance systems (VSSS) to monitor vaccines and inform the public of safety data. With little known about public attitudes, perceptions, and experiences with VSSS, we examined them in the context of COVID-19 vaccinations in Western Australia. Methods: Researchers conducted 158 qualitative interviews between March 2021 to May 2022 within the broader Coronavax project. Data regarding VSSS was coded in NVivo using deductive and inductive methods. Results: Despite some not knowing about VSSS, participants expected follow-up post COVID-19 vaccination. Vaccine hesitant or refusing participants knew about VSSS and regarded these systems positively. Additional considerations concerned the reliability of data collected by VSSS. Conclusion: Perceptions of VSSS signal a lack of understanding about how these systems work. Future studies should further explore the public's understanding of VSSS, whether VSSS improves vaccine confidence, and how governments can better communicate to the public about VSSS. Implications for public health: Lack of understanding of how VSSS operate may be stymying attempts to build public vaccine confidence. Healthcare providers and governments could build public knowledge and understanding of VSSS to mitigate concerns of AEFIs.